THE ROLE OF CROSS- CULTURAL FACTORS IN INTEGRATIVE CONFLICT RESOLUTION AND CRISIS COMMUNICATION BPODT: THE SIGAPITON LAND CONFLICT IN NORTH SUMATERA: PERAN FAKTOR LINTAS BUDAYA DALAM RESOLUSI KONFLIK INTEGRATIF DAN KOMUNIKASI KRISIS BPODT: KONFLIK TANAH SIGAPITON DI SUMATERA UTARA - Nauli Panjaitan, Tetti (LPPM UPMI, 2023)
This article offers an integrated theoretical and policy-oriented framework for cross-cultural conflict resolution by exploring the relationship between conflict resolution styles and a crisis communication strategy with an emphasis on conflict and structure cross-cultural factors. Conflict Handling with BPODT crisis communication against the law of the Sigapiton indigenous people as Sigapiton land owners as a case study, the factors inherent in the conflict are mixed with respect for the characteristics of the Batak culture. The suitability of the Batak cultural context with integrative conflict management is explored. This Research is qualitative research, in this article use media reports, documents and interview in collecting data. The analysis shows that the use mediators and consideration of cultural approaches and respect for the history of the people who live on Sigapiton land are resources in interpersonal interactions among the Sigapiton indigenous peoples, tending to contribute to integrative conflict solutions.